Our narrow hiding places : a novel - Jansma, Kristopher (Ecco, 2024)
"For fans of All the Light We Cannot See and The Nightingale: an elderly woman recounts her Dutch family's survival during the final years of Nazi occupation, shedding new light on old secrets that rippled through subsequent generations. Eighty-year-old Mieke Geborn's life is one of quiet routine. Widowed for many years, she enjoys the view from her home on the New Jersey shore, visits with friends, and tai chi at the local retirement community. But when her beloved grandson, Will, and his wife, Teru, show up for a visit, things are soon upended. Their marriage is threatening to unravel, and Will has questions for his grandmother-questions about family secrets that have been lost for decades and are now finally rising to the surface. But telling Will the truth involves returning to the past, and to Mieke's childhood in coastal Holland. There, in the last years of World War II, she survived the Hunger Winter, a brutal season when food and heat were cut off and thousands of Dutch citizens starved. Her memories weave together childhood magic and the madness of history, and carry readers from the windy beaches of The Hague to the dark cells of a concentration camp, through the bends of eel-filled rivers, and, finally, to the story of Will's father, absent since Will's childhood. Our Narrow Hiding Places is a sweeping story of survival and of the terrible cost of war-and a reminder that sometimes the traumas we inherit come along with a resilience we never imagined"--